Lead and its Health Hazards - Syed Sanowar Ali; Nasim Karim (Journal of Bahria University Medical and Dental College)
Metals are important source of pollutant toxicants which occur naturally in the environment. Now-a-days many metals have become essential to various biological processes and some level of human exposure is therefore unavoidable. Lead has been used by humans for at least 7000 years alone and in combination with other metals. It is highly toxic, ductile, malleable and easy to smelt. A wide range of adverse effects could be induced in human beings depending upon the dose and time period of lead exposure. Central nervous system of children is the most sensitive to lead effects while peripheral neuropathy, chronic nephropathy, and hypertension are the main concerns in adults. Other target tissues include the gastrointestinal, immune, skeletal, and reproductive systems. Effects on the heme biosynthesis provide a sensitive biochemical indicator even in the absence of other detectable effects. Present review is therefore written to provide comprehensive awareness regarding lead and its health hazards.